Generation of electron-acoustic waves in the magnetosphere - Singh, S. V.; Lakhina, G. S. (My University, 2001)
Generation of electron-acoustic waves (EAWs) is examined in an unmagnetized, four-component plasma consisting of stationary cold and hot Maxwellian electrons, drifting electron beam and ions. The addition of hot background electrons to the previously existing three-component model reduces the excited EAW frequencies and growth rates. Electrostatic linear dispersion equation is solved analytically for the growth rate and real frequency. The linear theory of EAWs is applied to the dayside auroral zone and other regions of the magnetosphere. The mechanism can generate frequencies over a wide range of Full-size image (<1 K)–Full-size image (<1 K), Full-size image (<1 K)–Full-size image (<1 K) and Full-size image (<1 K)–Full-size image (<1 K) in the dayside auroral zone, plasma sheet boundary layer and polar cusp, respectively. The e-folding time of the instability is of the order of a few milliseconds, and the waves are expected to grow nonlinearly to large amplitudes. Our four-component model can explain the broadband electrostatic noise (BEN) observations below the total electron plasma frequencies in these regions fairly well.
Keywords: Electron-acoustic waves; Magnetosphere; Earth's magnetosphere; Broadband electrostatic noise (BEN); EAW